Gender mainstreaming - Rey Aramendía, Matilde (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The article addresses the arising of gender mainstreaming as a transformative strategy to implement public equality policies. The emergence of this strategy should be understood as part of the development that public equality policies have undergone since its advent in the 1970s. Gender mainstreaming represents a great step forward, since it questions for the first the social, cultural, political and economic structures that perpetuates inequality, suggesting to transform them through the articulation of public policies. However, despite the initial enthusiasm, its practical results are far away from meeting its theoretical objectives, which has undoubtedly been the subject of the most serious criticism. Throughout these pages we attempt to provide the widest possible understanding of this strategy.